Pengembangan Media Video Animasi Menggunakan Powtoon pada Mata Pelajaran IPA Kelas VIII SMP - Arief Hendrawan; Alwen Bentri (Departement of Mathematics Education, 2023)
The aim of this research is to use Powtoon to produce animated video media for grade VIII SMP science class VIII. This type of research is Research and Development (R&D). The research model used is the 4-D development model (Four-D Models). The 4-D development model (Four-D Models) has four stages that must be carried out, namely definition, design, development and deployment. Research.and Development.(R&D) is the term.for this type of study. Development model.4-D is the research model used (Four-D Models). The four stages of the 4-D development model (Four-D Models) are definition, design, development, and deployment. The product validation test was carried out by three validators, namely one material validator and two media validators, while the practicality test was carried out by 26 students of class VIII A SMPN 1 Padang Panjang. Questionnaire sheets, documentation, and assessment formats are the assessment tools used.The results of the validity test showed that the material validation achieved an average result of 4.77 in the